2009
DOI: 10.1002/mawe.200800445
|View full text |Cite
|
Sign up to set email alerts
|

On impurities and the internal structure in precipitates occurring during the precipitation of nanocrystalline calcium phosphate

Abstract: Nanocrystalline calcium phosphate was precipitated at 20 C from calcium nitrate and ammonium phosphate solutions at a pH of 9 -11. The nature of the mass loss steps in thermogravimetry of the product was revealed by in-situ mass spectrometry of released gases upon heating. Major amounts of nitrate-containing impurities like NH 4 NO 3 and Ca(NO 3 ) 2 were present which could only be removed by multiple washing with water. These impurities were not crystalline, but they were clearly detectable in the infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…A broad band at 2800-3700 cm À 1 and a sharper one at 1630 cm À 1 are due to adsorbed and entrapped water [22]. A broad absorbance having top within 3100-3190 cm À 1 of NH 4 þ and a sharp and strong one at 1380 cm À 1 of NO 3 À are associated with the presence of the NH 4 NO 3 by-product (the samples were freeze-dried without washing) [23]. The strong absorbances of PO 4 3À at about 1040 cm À 1 (u 3 ) and 580 cm À 1 (u 4 ) are not resolved.…”
Section: Resultsmentioning
confidence: 99%
“…A broad band at 2800-3700 cm À 1 and a sharper one at 1630 cm À 1 are due to adsorbed and entrapped water [22]. A broad absorbance having top within 3100-3190 cm À 1 of NH 4 þ and a sharp and strong one at 1380 cm À 1 of NO 3 À are associated with the presence of the NH 4 NO 3 by-product (the samples were freeze-dried without washing) [23]. The strong absorbances of PO 4 3À at about 1040 cm À 1 (u 3 ) and 580 cm À 1 (u 4 ) are not resolved.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, both the exact structure and the chemical composition of this hydrated layer are still uncertain (regrettably, as the hydrated layer cannot be isolated, it is not possible to standardize the methods for detailed studies) [235,[237][238][239]. Nevertheless, it is known that the surface layer might adsorb considerable amounts of foreign compounds (molecules and ions) in the percent mass range [247]. Strictly speaking, all the aforementioned apply to both biological apatite of calcified tissues [248] and micron-sized apatites as well [249]; nonetheless, in nano-sized crystals, the composition of the hydrated surface layer contributes to the global composition for a non-negligible proportion.…”
Section: Compoundmentioning
confidence: 99%
“…Thereby, the composition of the product must be carefully controlled as it depends strongly on synthesis conditions and washing of the obtained precipitate. It has been shown that washing at least two times is needed for removal of NH 4 NO 3 if the synthesis is carried out in ammonia solution [11]. Most often, the phase composition of the products of synthesis is clarified on the basis of the composition of starting materials and X-ray diffraction (XRD) analysis or Fourier transform infrared (FTIR) spectroscopy/ Raman analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied successfully for the analysis of synthetic and natural bioapatites [11][12][13][14][15][16][17]. In some cases, TA-MS also allows to detect the origin of the decomposed component and its content and, therefore, to get information about the structure of the sample [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation